'The Revolution is to the human mind what the African sun is to vegetation': Revolution, heat, and the normal school project. (April 2021) - Warman, Caroline
This article focuses on a slightly earlier period in its investigation of the meanings of and associations with the term normal than Cryle and Stephens have done in their recent book. It looks at the establishment and rapid demise of the Ecole normale (normal school) in Paris in 1794–5, founded on the same model as a school for the manufacture of arms that had operated in spring 1794, and suggests that this model was not only responsible for some of the problems the Ecole normale experienced, setting up unachievable expectations of rapid efficacy, but also had an impact on what its name was assumed to mean. Moving between, on the one hand, an analysis of explicit (and opposing) definitions of what the term normal meant, and, on the other, an account of how the Ecole normale was set up and what it was set up to do, this paper agrees with Cryle and Stephens that the term was 'formed in controversy', and fills in the intellectual and philosophical context from which the notion of the statistical norm would emerge.